Scrophularia lucidaifolia (Scrophulariaceae), a new species from Turkey - Özbek, Funda; Bi̇lgi̇li̇, Bi̇lgehan; Uzunhisarcikli, Mehmet Erkan; Guner, Ebru (Magnolia Press, 2015)
The genus Scrophularia Linnaeus (1753: 619) (Scrophulariaceae) is represented by approximately 270 taxa (species and subspecies) worldwide (Olivencia 2009). It is restricted primarily to the North Temperate Zone (Carlbom 1968). The primary centre of diversity of Scrophularia is located in the Irano-Turanian region. The Mediterranean region is also an important area of diversity and for the endemism rate of Scrophularia (Scheunert & Heubl 2014).
Keywords: 15. Life on land